Proatherogenic or antiatherogenic high density lipoprotein type in acute coronary syndrome and healthy male person (Medical Journal of Indonesia, 2010)
Aim: To make proatherogenic/antiatherogenic HDL type criteria using Apolipoprotein A-I (ApoA-I), Paraoxonase-1 (PON-1), Neopterin and HDL-cholesterol levels, which may be useful in clinical practice.Methods: This was a case control study recruiting 52 subjects with Acute Coronary Syndrome (ACS) and 30 control healthy subjects. HDL type was classifi ed into antiatherogenic andÂ  proatherogenic based on the levels of ApoA-I, PON-1, Neopterin and HDL-cholesterol. Concentrations of ApoA-I was measured by immunoturbidimetry method, PON-1 was measured by colorimetric method, Neopterin was measured by ELISA, and HDL-C was determined by homogenous method. Univariate logistic regression analysis was done using ACS as a dependent variable and levels of ApoA-I, PON-1, Neopterin andHDL-cholesterol as independent variables. Proatherogenic/ antiatherogenic HDL type was determined by using ApoA-I, PON-1, Neopterin and HDL-cholesterol cut off and odd ratios.Results: Patientâs age was 50.89 + 12.63 year, HDL-C was 39.82 + 9.84 mg/dL, Apo A-1 was 119.77 + 32.05 mg/ dL, PON-1 was 41.26 + 18.19 kU/L, Neopterin was 16.22 + 38.10 nmol/L. Cut offs of ApoA-I, PON-1 and Neopterin successively were 124.5 mg/dL, 40.8 kU/L, and 7.016 nmol/L. On univariate logistic regression analysis showed that OR of ApoA-I, PON-1 and Neopterin respectively were 29.759 (95% CI : 4.074 â 217.382), 1.647 (95% CI : 0.412 â 6.586), 4.317 (95% CI : 1.098 â 16.977). Using scoring system, we concluded that total score > 18 was proatherogenic HDL type, and total score < 18 was antiatherogenic HDL type. With this scoring we found 78.85% had proatherogenic HDL type in ACS population.Conclusions: Dysfunctional HDL or proatherogenic/anti atherogenicÂ  HDL type can be predicted by using ApoA-Iâ PON-1âNeopterinâHDL-cholesterol scoring system. Those with score of 18 are supposed to have antiatherogenic HDL type, and those with score of > 18 were having proatherogenic HDL type. (Med J Indones 2010; 19:228-34)Keywords: ApoliproteinA-I (ApoA-I), HDL-cholesterol, neopterin, paraoxonase-1 (PON-1), proatherogenic/antiatherogenic HDL